2020
DOI: 10.3390/app10165604
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Heat Treatments on Torsional and Cyclic Fatigue Resistance of Nickel–Titanium Rotary Files: A Comparative Study

Abstract: Protaper Universal (PTU), Protaper Gold (PTG) (Maillefer, Ballaigues, CH), EdgeTaper (ET), and EdgeTaper Platinum (ETP) (Albuquerque, NM, USA) were tested for both torsional and flexural resistance. The aim of the present study was to evaluate the influence of proprietary heat treatment on the metallurgical properties of the aforementioned instruments. Four groups of 30 different instruments (size 20.07) were tested, then divided into two subgroups of 15 instruments—one for the cyclic fatigue test in a curved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 29 publications
(30 reference statements)
1
19
0
Order By: Relevance
“…Finally, the second group consists of all those structural factors that characterize an endodontic instrument, such as the cross-sectional design, the type of the alloy and its crystallography phase, the manufacturing processes, the pitch, the helix and the rake angle, the length of the instrument and the taper [ 49 , 55 , 62 , 63 , 64 ]. As many studies have shown, the design of the cross-section is one of the most important parameters that can significantly determine the torsional stiffness of a NiTi endodontic instrument, since it thoroughly influences its mechanical properties [ 62 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the second group consists of all those structural factors that characterize an endodontic instrument, such as the cross-sectional design, the type of the alloy and its crystallography phase, the manufacturing processes, the pitch, the helix and the rake angle, the length of the instrument and the taper [ 49 , 55 , 62 , 63 , 64 ]. As many studies have shown, the design of the cross-section is one of the most important parameters that can significantly determine the torsional stiffness of a NiTi endodontic instrument, since it thoroughly influences its mechanical properties [ 62 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the different instruments Hyflex CM and One Curve showed the best mechanical rotating behaviors. Recent in vitro investigations [39] confirmed, from a mechanical viewpoint, the influence of different heat treatments on the torsional and cyclic fatigue resistance of rotary instruments.…”
Section: Discussionmentioning
confidence: 88%
“…4,6 For this reason, in recent literature many studies focused their attention on NiTi torsional behavior. 7,8 Recent studies investigated the role of two prevailing factors affecting torsional resistance, that is, heat treatments and the metal mass of the instrument. [7][8][9] According to the most recent literature, static torsional resistance tests have been evaluated as described by International Organization for Standardization (ISO) 3630-1.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Recent studies investigated the role of two prevailing factors affecting torsional resistance, that is, heat treatments and the metal mass of the instrument. [7][8][9] According to the most recent literature, static torsional resistance tests have been evaluated as described by International Organization for Standardization (ISO) 3630-1. According to this, to evaluate torsional resistance, a stainless steel (SS) instrument is rotated at 2 rpm with its tip blocked at 3 mm until fracture and the torque generated is calculated by a torque meter.…”
Section: Introductionmentioning
confidence: 99%